Eksistensi Program Religi Sasisoma Dalam Radio Geronimo FM Dalam Mengenalkan Nilai Islam Di Era New Media - Zahrotus Saidah; Wijayanti, Tria (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2023)
This research is based on the researcher's interest in the existence of the Sasisoma program on Radio Geronimo FM, Yogyakarta. In the new media era, almost all society no longer listens to the radio due to the advancement of digital media that provides numerous entertainment and educational content platforms. Therefore, this study aims to explore how the Sasisoma program introduces Islamic values and maintains its existence in the new media era. The research employs a qualitative method with a descriptive approach to systematically depict the facts pertaining to the subject and object at Radio Geronimo, with a focus on the intended research. The data collection techniques include participant observation, semi-structured interviews with the main informant Leila Karina, supporting informant Munif Tauchid, and documentation.To ensure data validity, the researcher employs source triangulation and time triangulation, utilizing the AIDDA theory. The results of this research indicate that the efforts of the Sasisoma program to sustain its existence in the new media era include generating Attention by creating compelling da'wah content and publishing it on social media. Subsequently, Interest is aroused by the broadcasters delivering contemporary da'wah content, leading to Desire through interaction. The Decision phase involves collaborating on digital media platforms, and finally, Action is taken by receiving likes, comments, and shares on the posts.